2009
DOI: 10.1007/s00213-009-1550-3
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine transporter gene polymorphisms affect susceptibility to depression and predict antidepressant response

Abstract: Our study revealed a positive association of the NET-T182C polymorphism with susceptibility to and severity of depression, and a positive association between the 5-HTT polymorphisms and the antidepressant response to SSRI. Combinations of these polymorphisms provided some potential gene-gene interaction effects. These findings might be of some clinical values in optimization of depression treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 48 publications
3
33
1
2
Order By: Relevance
“…It was reported that the STin2 polymorphism can play a role as a risk factor in MDD [198][199][200] and suicidal behaviour, 201,202 creating a synergistic effect with 5-HTTLPR. 203 The STin2 polymorphism seems to also affect antidepressant response, as reported by different authors, 85,175,182,191 and it was proposed that a STin2 10/12 genotype (where 10/12 indicates the number of repeats in the 2 alleles) may be associated with a poorer antidepressant effect, especially in Asian populations. 204 Some studies were not able to replicate these findings.…”
Section: Comtmentioning
confidence: 88%
See 2 more Smart Citations
“…It was reported that the STin2 polymorphism can play a role as a risk factor in MDD [198][199][200] and suicidal behaviour, 201,202 creating a synergistic effect with 5-HTTLPR. 203 The STin2 polymorphism seems to also affect antidepressant response, as reported by different authors, 85,175,182,191 and it was proposed that a STin2 10/12 genotype (where 10/12 indicates the number of repeats in the 2 alleles) may be associated with a poorer antidepressant effect, especially in Asian populations. 204 Some studies were not able to replicate these findings.…”
Section: Comtmentioning
confidence: 88%
“…[176][177][178][179][180] On the other hand, studies involving Asian populations usually report conflicting results: some studies reported that the short 5-HTTLPR allele was associated with better outcomes, [181][182][183][184] some found no effect of 5-HTTLPR genotype on treatment efficacy 121,185,186 and some reported that the long 5-HTTLPR allele was associated with better outcomes. 83,[187][188][189][190][191] Interestingly, Lotrich and colleagues 192 recently reported that paroxetine blood concentration was positively associated with HAM-D response in a sample of elderly patients, but this association was found to be significant only in carriers of the short allele. In contrast, when augmentation strategies have been investigated, the short allele has been associated with a better response in patients prescribed pindolol or lithium.…”
Section: Comtmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, polymorphisms in the SLC6A4 gene were associated with antidepressant response or remission [28,68,76,81,88,91]. Similar SLC6A4 variants have shown an association with lithium treatment outcomes in patients with BPD [75,102].…”
Section: Lithium Treatment For Bipolar Disordermentioning
confidence: 97%
“…Another polymorphism influencing SERT expression, described as 17bp VNTR polymorphism, was identified within intron 2 (STin2) [80]. Several studies reported an influence of STin2 on response to ADs, but other investigations were not able to repeat these findings [81][82][83][84][85]. Moreover, it was proposed that STin2 10/12 genotype may be associated with poorer antidepressant effect, especially in Asian populations [86].…”
Section: Serotonin Transporter (Slc6a4)mentioning
confidence: 99%